2018
DOI: 10.1088/1757-899x/395/1/012022
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Mechanical Properties and Relaxation Time of Agar Hydrogel for Tissue Mimicking Phantom Material in Magnetic Resonance Imaging

Abstract: Agar hydrogel is used for tissue mimicking phantom in magnetic resonance imaging studies. The spin-lattice relaxation time, T1 as an important parameter in Magnetic Resonance Imaging measurement was observed. The T1-value represents how fast the net spin magnetization vector recovers to its equilibrium after generation of magnetic field. To explore mechanical properties of agar, shear modulus was examined using a dynamic mechanical analyser. The relation between mechanical properties and spin-lattice relaxatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…This trend can be observed in all agar gel phantoms with the addition of Fe 2 O 3 as a relaxation modifier. Pure agar hydrogel and agarose gel phantoms in other studies have exhibited a similar trend of SNR signal reduction as TE increased with T2 values of 116.71 ms and 150.00 ms, respectively [5,19]. The T2 values of the agar gel phantoms in this study are still in the range of T2 for human tissues (40-150 ms) [1].…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…This trend can be observed in all agar gel phantoms with the addition of Fe 2 O 3 as a relaxation modifier. Pure agar hydrogel and agarose gel phantoms in other studies have exhibited a similar trend of SNR signal reduction as TE increased with T2 values of 116.71 ms and 150.00 ms, respectively [5,19]. The T2 values of the agar gel phantoms in this study are still in the range of T2 for human tissues (40-150 ms) [1].…”
Section: Discussionsupporting
confidence: 69%
“…This creates a high barrier for hydrogen spins to move resulting in a shorter T1. It has also been reported that high gel phantom concentrations resulted in low T2 due to its low water content after evaporation, indicating less dipole-dipole interaction for the mechanism of T2 relaxation [4,19]. In this study, the concentration of agar gel phantoms was fixed at 0.03 gml −1 ; hence, any change in T1 and T2 relaxations within and between TP1 and TP2 was not attributed to the concentration of the gelling agent.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations